Kontribusi Kualitas Sumber Daya Manusia Kepala Desa terhadap Pencapaian Desa Mandiri - Ali Hanafiah Muhi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
The limited availability of quality human resources within the bureaucracy, particularly in village governments, often results in stagnation and delays in achieving Independent Village status. One of the primary challenges faced by villages in Indonesia is the relatively low quality of village heads’ human resources. This study employs a quantitative research approach, utilizing documentation studies for data collection and simple statistical tests for analysis. The findings were then interpreted, discussed, and concluded. The study reveals that, as of 2023, the Special Region of Yogyakarta (D.I. Yogyakarta) had the highest proportion of village heads with Doctoral (S3) and Master’s (S2) degrees, correlating with the successful attainment of Independent Village status. Gorontalo Province, with the highest percentage of village heads holding Bachelor’s (S1) and Diploma (D.IV) degrees, achieved Advanced Village status. Similarly, the Riau Islands Province, with a predominance of village heads educated to the Senior High School level or equivalent, also attained Advanced Village status. Conversely, West Papua Province, characterized by the highest percentage of village heads with education below Senior High School, remained categorized as a Disadvantaged Village. These findings underscore the significant impact of village heads’ educational qualifications on the Village Development Index (VDI) growth and scores. Village heads with higher education levels (S3, S2, S1, and Diploma) and those with high school or equivalent education positively influence VDI growth rates and scores. In contrast, village heads with education levels below Senior High School demonstrate slower and lower VDI growth rates. This highlights the crucial role of high-quality village heads in advancing village development, accelerating progress, and achieving Independent Village status.